Postural and Cortical Responses Following Visual Occlusion in Adults With and Without ASD - Goh, K.; Morris, Susan; Parsons, R.; Ring, A.; Tan, Tele (Springer New York LLC, 2017)
© 2017 Springer Science+Business Media, LLC, part of Springer Nature Autism is associated with differences in sensory processing and motor coordination. Evidence from electroencephalography suggests individual perturbation evoked response (PER) components represent specific aspects of postural disturbance processing; P1 reflects the detection and N1 reflects the evaluation of postural instability. Despite the importance of these cortical responses to postural control, PERs to a perturbation in adults with autism spectrum disorder (ASD) have yet to be reported. The aim was to compare PERs to visual perturbation under varied postural stability conditions in adults with and without ASD. This study is the first to report that while the assessment of postural set is intact, adults with ASD use more cortical resources to integrate and interpret visual perturbations for postural control.